IMPLEMENTASI TEXT TO SPEECH DALAM APLIKASI PEMBELAJARAN MATEMATIKA DASAR DENGAN AUGMENTED REALITY - Fu’adah Amran, Hasanatul; Medikawaty Taufiq, Reny; Asrul Abdurrahim, Abulkhair; Mukhtar, Harun (Department of Information System Muhammadiyah University of Riau, 2022)
Mathematical science is a basic science that supports other sciences in its application. Therefore, understanding mathematics correctly will have implications for the ability to study several sciences related to mathematics. This study developed an augmented reality-based basic math learning application that can provide education to students with different media in order to increase student interest in learning mathematics. This application uses the Vuforia SDK library which is able to display 3-dimensional characters with markerless techniques in the form of augmented reality. The final result of this study is an application that can be used on smartphones with the Android operating system, based on the results of testing the application, it is concluded that the research and development of basic mathematics learning applications based on augmented reality have been successfully implemented and a series of tests have been carried out to test the capabilities of the application. From the results of testing conducted by distributing questionnaires to students who are sitting in elementary school, from grade 3 (three) to grade 6 (six). The result of the percentage of students' answers who answered correctly was 97 percent (%) and the wrong one was 3 percent (%), it can be concluded that the application of basic mathematics learning based on augmented reality can help students in learning mathematics with learning media and can help students learn math anywhere easily.